Life-view Scale: development and validation among a sample of Kurdish university students and lecturers. Issue 8 (14th September 2021) - Ismail, Azad Ali
ABSTRACT: This study aimed to develop and validate the Life-view Scale. In study one, a sample of 182 university students completed the questionnaire. The scale had good internal consistency (alpha = .81). Exploratory factor analysis of the initial scale resulted in five factors (satisfaction, purpose, search, direction, and doubt). Factors were significantly inter-correlated, except the Doubt factor which was not correlated with Search and Direction factors. In study two, a sample of 59 university students participated in answering the questionnaire on two occasions with an interval of 15 days. The test–retest correlation of the questionnaire was good ( r = .81). In study three, a sample of 71 university lecturers completed the questionnaire alongside measures of burnout and job satisfaction. The Life-view Scale was found to be positively correlated to job-satisfaction only. In summary, the Life-view Scale was found to possess satisfactory measures of internal reliability, temporal stability, and convergent validity.